Lithological and hydrochemical controls on distribution and speciation of uranium in groundwaters of hard-rock granitic aquifers of Madurai District, Tamil Nadu (India) - Thivya, C.; Chidambaram, S.; Keesari, T.; Prasanna, Mohan Viswanathan; Thilagavathi, R.; Adithya, V.; Singaraja, C. (Springer, 2016)
Uranium is a radioactive element normally present in hexavalent form as U(VI) in solution and elevated levels in drinking water cause health hazards. Representative groundwater samples were collected from different litho-units in this region and were analyzed for total U and major and minor ions. Results indicate that the highest U concentration (113 µg l-1) was found in granitic terrains of this region and about 10 % of the samples exceed the permissible limit for drinking water. Among different species of U in aqueous media, carbonate complexes [UO2(CO3)22-] are found to be dominant. Groundwater with higher U has higher pCO2 values, indicating weathering by bicarbonate ions resulting in preferential mobilization of U in groundwater. The major minerals uraninite and coffinite were found to be supersaturated and are likely to control the distribution of U in the study area. Nature of U in groundwater, the effects of lithology on hydrochemistry and factors controlling its distribution in hard rock aquifers of Madurai district are highlighted in this paper.